Immunoglobulin G4-Related Disease Accompanied by Primary Myelofibrosis: Case Report - Liu, Ziwei; Zhang, Shangzhu; Zhang, Wen; Feng, Jun; Li, Mengtao; Zeng, Xiaofeng (Frontiers in Medicine, 2021)
Immunoglobulin G4 related disease (IgG4-RD) is a heterogeneous autoimmune fibrosing disorder that presents common pathologic features but with unclear etiology. We report a rare case with IgG4-RD accompanied by primary myelofibrosis that eventually transformed into acute myeloid leukemia. A 50-year-old woman suffered from progressive lacrimal and parotid glands enlargement, diaphoresis, and rapid weight loss. Important clinical findings included remarkable leukocytosis, hyperglobulinemia, and splenomegaly. IgG4-RD was confirmed by salivary gland biopsy. Meanwhile, myelofibrosis was diagnosed according to histopathological findings of bone marrow and genetic mutations test of peripheral blood. The patient was on corticosteroid treatment. However, she developed into acute myeloid leukemia (AML) in the 8th month of follow-up. Our case suggested that myeloproliferative neoplasm (MPN) may co-occur with IgG4-RD. Bone morrow aspiration and genetic tests are helpful for throughout evaluation. An active search for hematological malignancies is warranted at diagnosis and during follow-up for patients who present with unexplained leukocytosis, pancytopenia, splenomegaly, or weight loss.